PENGARUH IKLIM KERJA DAN KEPUASAN KERJA TERHADAP LOYALITAS KERJA PADA GURU SMA NEGERI DI KECAMATAN NUSANIWE KOTA AMBON - Jermanto Subeno Lasamahu (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effects of teachers’ work climate and job satisfaction, both partially and simultaneously, on teachers’ work loyalty at public senior high schools in Nusaniwe District, Ambon City. Teachers’ work loyalty is understood as a form of professional commitment and responsibility toward the school organization, which is influenced by the prevailing work climate and the level of job satisfaction perceived by teachers. This study employed a quantitative approach with a correlational design. The research population consisted of 141 civil servant teachers and non-permanent teachers at three public senior high schools in Nusaniwe District, with a sample of 104 respondents determined using the Slovin formula. Data were collected through questionnaires and analyzed using simple linear regression and multiple linear regression. The results indicate that teachers’ work climate has a positive and significant effect on teachers’ work loyalty, contributing 51.5%, while teachers’ job satisfaction contributes 63.3%. Simultaneously, both variables have a significant effect on teachers’ work loyalty with a contribution of 63.5%. The novelty of this study lies in the simultaneous examination of these two variables within the context of public senior high schools in Nusaniwe District, Ambon City.